Formation, Growth, or Rupture of De Novo Intracranial Aneurysms: Long-Term Follow-up Study of Subarachnoid Hemorrhage Survivors. Issue 6 (11th October 2021) - Han, Hyun Jin; Lee, Woosung; Kim, Junhyung; Park, Keun Young; Park, Sang Kyu; Chung, Joonho; Kim, Yong Bae
Abstract: BACKGROUND: The survival rate of aneurysmal subarachnoid hemorrhage (aSAH) has gradually increased, leading to more clinical cases of de novo intracranial aneurysms (DNIAs). OBJECTIVE: To identify the characteristics of patients with DNIA growth or rupture. METHODS: We included 1601 patients with aSAH treated by clipping from January 1993 to May 2010. According to the inclusion and exclusion criteria, 233 patients had no DNIAs, and 63 patients had 77 DNIAs. We assessed the incidence rate of DNIAs and risk factors for DNIA formation. After dichotomizing the DNIA group into the heed (patients with DNIA rupture or growth) and stable groups (patients without DNIA growth), we assessed the risk factors for DNIA growth or rupture. RESULTS: The total follow-up period was 4427.9 patient-years. The incidence rate per patient-year was 1.42%. Age ≤50 yr, family history of aneurysm, and multiplicity at initial aSAH were significant risk factors for DNIA formation. Multivariate regression analysis revealed that female sex (odds ratio [OR], 5.566; 95% confidence interval [CI], 1.241-24.952), duration from initial aSAH to DNIA detection <120 mo (OR, 5.043; 95% CI, 1.362-18.668), multiplicity at initial aSAH (OR, 4.859; 95% CI, 1.207-19.563), and maximum DNIA diameter ≥4 mm (OR, 11.104; 95% CI, 2.337-52.772) were significant risk factors for DNIA growth or rupture. CONCLUSION: DNIAs had a higher incidence rate than expected. Taking into account the presented incidence rate and risk factors, long-term surveillance in aSAH survivors for more than a decade may be worth considering, at least on a case-by-case basis. Graphical Abstract: